DRAMATURGICAL ANALYSIS OF VLOGGER’S IMPRESSION MANAGEMENT ON SOCIAL MEDIA - Krisnawati, Ester (Universitas Muhammadiyah Yogyakarta, 2020)
The presence of social media is not only used by someone to communicate with other people but also to present oneself with certain goals. The appearance of celebgram and vloggers has shown that social media is a place to show oneself in front of others. This study aims to describe the impression management vlogger in the